2019
DOI: 10.3390/rs11182077
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Data Fusion for Satellite Images Using Hopfield Neural Network

Abstract: Spatio-temporal data fusion refers to the technique of combining high temporal resolution from coarse satellite images and high spatial resolution from fine satellite images. However, data availability remains a major limitation in algorithm development. Existing spatio-temporal data fusion algorithms require at least one known image pair between the fine and coarse resolution image. However, data which come from two different satellite platforms do not necessarily have an overlap in their overpass times, henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Since then, literature [6] uses colour histograms as target features to achieve tracking of nonrigid targets, but the problem with this algorithm is that the tracker cannot track the target correctly when the target and the background are similar. Literature [7] uses the method of fusion of colour feature and direction feature to track the target, but this algorithm is not able to track the target well under the condition of scene change. Literature [8] fused colour features and texture features of LBP in a Bayesian framework and used particle filter algorithms for state estimation, which is robust to the deformation and occlusion challenges of the target.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, literature [6] uses colour histograms as target features to achieve tracking of nonrigid targets, but the problem with this algorithm is that the tracker cannot track the target correctly when the target and the background are similar. Literature [7] uses the method of fusion of colour feature and direction feature to track the target, but this algorithm is not able to track the target well under the condition of scene change. Literature [8] fused colour features and texture features of LBP in a Bayesian framework and used particle filter algorithms for state estimation, which is robust to the deformation and occlusion challenges of the target.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [17] proposed a spatial and temporal reflectance unmixing model (STRUM) algorithm based on the decomposition of mixed pixels and applied it to the normalized difference vegetation index (NDVI) remote sensing image fusion, found that the fusion result of STRUM is better than STARFM. The authors in [18] proposed a spatial and temporal data fusion model (STDFA) based on the temporal change characteristics of pixel reflectivity and the texture characteristics of mediumresolution images method, and the spatial and temporal data fusion model (STDFA) is reconstructed on the NDVI data in Jiangning District, Nanjing. The above spatio-temporal fusion algorithm has been widely used in land surface temperature monitoring [19,20], vegetation change monitoring [21], crop growth monitoring [22,23], etc., but few people in China apply it to flood monitoring, and almost no scholar has explored the applicability of different types of spatiotemporal fusion algorithms in flood monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithms require building a correspondence between Landsat and MODIS images through learning a dictionary pair resulting in enhancing the spatial resolution of MODIS images to the Landsat spatial resolution. Other approaches for data fusion rely on sophisticated machine learning methods such as convolutional neural networks (CNN), Hopfield neural networks (HNN) and random forests (RF) ( Song et al, 2018 ; Fung et al, 2019 ; Ke et al, 2016 ) to find the relationship between fine and coarse satellite images.…”
Section: Introductionmentioning
confidence: 99%